A propensity-matched comparison of long-term disability worsening in patients with multiple sclerosis treated with dimethyl fumarate or fingolimod. (June 2021) - Salter, Amber; Lancia, Samantha; Cutter, Gary; Marrie, Ruth Ann; Mendoza, Jason P.; Lewin, James B.; Fox, Robert J.
Background: Although the aggregate of data among patients with multiple sclerosis (MS) have shown similar efficacy between dimethyl fumarate (DMF) and fingolimod (FTY), most studies have not assessed long-term worsening of disability. We compared long-term disability worsening over 5 years, as assessed by the Patient-Determined Disease Steps (PDDS), among participants with MS treated with DMF or FTY. Methods: We identified individuals in the North American Research Committee on Multiple Sclerosis (NARCOMS) registry who had relapsing-remitting MS (RRMS), residing in the United States (Spring 2011 to Spring 2018), who initiated treatment with DMF ( n = 689) or FTY ( n = 565) and had ⩾1 year follow-up on index treatment. Participants receiving DMF who were previously treated with FTY and those on FTY previously treated with DMF were excluded. Propensity score matching at baseline was used to match FTY-treated to DMF-treated participants. Time to 6-month confirmed disability worsening (⩾1-point increase on PDDS, sustained for ⩾6 months) was estimated using Cox regression. A sensitivity analysis was conducted to account for differences in the duration of index exposure between DMF and FTY groups. Results: After propensity score matching, 468 DMF-treated participants were matched with 468 FTY-treated participants. Median treatment duration was 3.0 years for DMF and 4.0 years for FTY. At 5 years, 68.3% [95% confidence interval (CI): 62.4–73.5] of DMF-treated participants and 63.3% (95% CI: 59.6–70.1) treated with FTY were free from 6-month confirmed PDDS worsening [hazard ratio (HR) 1.01 (95% CI: 0.79–1.28); p = 0.95]. Results were similar in the sensitivity analysis: 70.5% (95% CI: 61.8–77.6) of DMF-treated participants and 72.7% (95% CI: 65.4–78.6) of FTY-treated participants were free from 6-month confirmed PDDS worsening [HR: 1.04 (95% CI: 0.71–1.51); p = 0.84]. Conclusions: In participants with MS from the NARCOMS registry, there was no significant difference in confirmed disability (PDDS) worsening over 5 years between those treated with DMF versus FTY.